Post-harvest assessment of tangerina ‘Dekopon’ fruits submitted to ultraviolet radiation C, passive modified atmosphere and benefit (Research, Society and Development, 2020)
Tangerines have been gaining more and more market share, sharing space with oranges, showing themselves as a strong economic factor, mainly due to consumer preference for this product. However, studies are needed that can maintain the post-harvest quality of the fruit in an economical and efficient way. Therefore, the objective of this study was to evaluate physically and chemically the fruits of the 'Dekopon' tangerine variety, analyzing the influence of the presence and absence of processing and ultraviolet C (UVC) radiation, combined with three different packages under passive modified atmosphere (control , LDPE and EPS + PVC). The experiment was carried out in a completely randomized design (DIC) and 3 replications, using a 2x2x3x5 factorial scheme, with the presence and absence of beneficiation, application of 0 and 10 minutes of UVC radiation, passive modified atmosphere (control, LDPE, EPS + PVC) and days of analysis (0, 7, 14, 21 and 28 days), respectively. The data originated from the analyzes were submitted to analysis of variance (P